PARTISIPASI MASYARAKAT DALAM REVITALISASI PASAR PETERONGAN DI KOTA SEMARANG - Maria Palupi Sandharini; Aufarul Marom (Journal of Public Policy and Management Review, 2016)
A market is the area of trading goods by the seller more than one good called as shopping center , markets , shops , mall , plasa , trade center and other appellation ( ministerial regulation number 70 years 2013 on guidelines arrangement and training markets , shopping malls and ) modern store . At this time , market developments very rapidly in almost every region .Each region are racing to make market area as a source of revenue ( pad ) in the form of levies .According to regional regulations semarang city no 9 2013 on regulating the traditional markets , chapter iv market management planning part 1 article 9 about the physical development of the market building paragraph 1 as market buildings which consists of the main building and other facilities with marketing attention to the aspirations of local traders . In revitalization peterongan market is also need the support of the or community participation in regulation in semarang no 9 years 2013 about setting markets, section vi the role of the community article 41 (paragraph 1 and 2 ) (.This study adopted qualitative approaches to techniquedescriptive data collection the observation, interviews and study documents. Results in the research indicated that public participation in the revitalization of pasarpeterongan already have not run well. This is evidenced by the lack of the role of the community to participate in the peterongan this market and the lack of support from the markets.The research can be seen also that public participation by the market revitalization peterongan itself. Aspects viewed in research public participation in the revitalization of pasarpeterongan in the city semarang this is mind, power, expertise, and money. Government, traders and citizens should be cooperative and pull in together to support the project of peterongan market in the city of semarang so that the implementation become more optimal.